Family Values among Youth in Bosnia and Herzegovina - Dudić-Sijamija, Anida (Context: Journal of Interdisciplinary Studies, 2025)
This paper aims to contribute to a better understanding of how young people in Bosnia and Herzegovina perceive and value family-related norms, with a focus on the relationship between traditional collectivist and modern individualist attitudes. The research was conducted using a quantitative method, applying the “Family Values Scale” questionnaire on a convenience sample of 305 young individuals from various regions of Bosnia and Herzegovina. The findings indicate that young people in Bosnia and Herzegovina are increasingly embracing modern values, particularly in the context of individualism and freedom of choice, while simultaneously maintaining traditional views, especially regarding the distribution of power within the family. Although modernization shapes the value orientations of young people, deeply rooted traditions still exert a significant influence on their attitudes and behaviors, suggesting the coexistence of traditional and modern values within the generational discourse.